Hepatectomy Versus Hepatectomy With Lymphadenectomy in Hepatocellular Carcinoma. Issue 6 (July 2015) - Wu, Xianqiu; Li, Binkui; Qiu, Jiliang; Shen, Jingxian; Zheng, Yun; Li, Qijong; Liao, Yadi; He, Wei; Zou, Ruhai; Yuan, Yunfei
<x xml:space="preserve">Abstract</x> Goals and Background: The role of preventive lymphadenectomy has not yet been determined for hepatocellular carcinoma (HCC) patients. We designed a study to evaluate the effect of hepatectomy combined with preventive lymphadenectomy on HCC patients. Study: Patients were randomly divided into group A (treated with hepatectomy alone) and group B (underwent hepatectomy combined with lymphadenectomy). The postoperative complications and oncologic prognoses were analyzed. Results: Of the 85 patients enrolled into this study, 79 cases (38 in group A and 41 in group B) were pathologically confirmed to have HCC and received curative resection. One hundred and sixteen lymph nodes were dissected and evaluated as negative by the pathologist. The 12-, 36-, and 60-month disease-free survival rates of group A were 81.6%, 68.4%, and 63.2%, respectively, whereas they were 78.0%, 65.9%, and 63.4%, respectively, for group B. The 12-, 36-, and 60-month overall survival rates in group A were 94.7%, 78.9%, and 65.8%, respectively, whereas they were 87.8%, 78.0%, and 70.7%, respectively, in group B. The differences in the disease-free survival and overall survival between the 2 groups were not statistically significant according to the log-rank test (P=0.811 and P=0.881, respectively). The difference in the surgical complication rate between groups A and B was not statistically significant (47.4% vs. 36.6%, P=0.332). Conclusions: Although hepatectomy combined with regional lymphadenectomy is a safe procedure, preventive lymphadenectomy may not decrease the rate of tumor recurrence nor improve the prognosis in early-stage HCC patients.